2021
DOI: 10.1038/s41598-021-02454-1
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin derivative ST09 modulates the miR-199a-5p/DDR1 axis and regulates proliferation and migration in ovarian cancer cells

Abstract: Ovarian cancers are among the fatal malignancies affecting women globally, mainly due to their metastatic and chemoresistant nature. In this study, we report a potent curcumin derivative ST09 effective against ovarian cancers. Prior in-vitro studies with ST09 drug showed cytotoxicity in tumorigenic cells compared to normal cells and in-vivo, significant tumor reduction was observed with least systemic toxicity. ST09 induced cytotoxicity in the ovarian cancer cells triggering mitochondria-mediated intrinsic apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The upregulation of miR-192 observed in cisplatinresistant lung cancer cells was reversed by curcumin-induced inhibition of the NF-κB signaling pathway . The mi-RNA-transcriptome profiling of ovarian cancer cells treated with the curcumin analog ST09 (Table 1) also confirmed the downregulation of EMT pathways, identifying the miR-199a-5p/ DDR1 axis as an important target (Ravindran et al, 2021). Finally, among miRNAs that play a tumor-suppressing role, Wang et al reported the upregulation of miR-206 in curcumin-treated lung cancer cells (Wang N. et al, 2020), the inhibition of the PI3K/AKT/mTOR signaling pathway suppressing migration and invasion.…”
Section: Non-coding Rnas As New Targets Of Curcuminoidsmentioning
confidence: 67%
See 1 more Smart Citation
“…The upregulation of miR-192 observed in cisplatinresistant lung cancer cells was reversed by curcumin-induced inhibition of the NF-κB signaling pathway . The mi-RNA-transcriptome profiling of ovarian cancer cells treated with the curcumin analog ST09 (Table 1) also confirmed the downregulation of EMT pathways, identifying the miR-199a-5p/ DDR1 axis as an important target (Ravindran et al, 2021). Finally, among miRNAs that play a tumor-suppressing role, Wang et al reported the upregulation of miR-206 in curcumin-treated lung cancer cells (Wang N. et al, 2020), the inhibition of the PI3K/AKT/mTOR signaling pathway suppressing migration and invasion.…”
Section: Non-coding Rnas As New Targets Of Curcuminoidsmentioning
confidence: 67%
“…The subcellular targets of 16 curcumin analogs have more specifically been reviewed (Adeluola et al, 2021), while complementary data on EMT potential targets for eight additional analogs are summarized in Table 1. In this field, the targeting of EMT pathways by curcumin analogs such as ST09 produced a significant reduction in tumor growth without any adverse systemic toxicity in vivo (Ravindran et al, 2021). Hypoxia and the HIF signaling pathway led to enrichment in CSCs, and curcumin/curcuminoid effects against cancer EMT are mediated through its action on this major tumor microenvironment factor, through a decrease in the expression of miR-21, miR-210, IL-6, HIF-1α, and VEGF (Bao et al, 2012b).…”
Section: Molecular and Cellular Cancer Emt: Targets Of Curcuminoidsmentioning
confidence: 99%
“…In breast cancer, it acts by upregulating miR-34a [ 83 ], miR-132 and miR-502c [ 84 ], miR-181b, miR-34a, miR-16, miR-15a, and miR-146b-5p, and by downregulating miR-19a and miR-19b [ 85 ], while in recent studies several other miRs were added to the list, either involving curcumin or its synthetic analogs [ 86 , 87 , 88 ]. In gastric cancer cells, similarly to breast cancer, curcumin enhances miR-34a expression [ 89 ] but inhibits miR-21 [ 90 ], which has also been reported in other cancer types (see below); in lung cancer it downregulates miR-186 [ 91 ] and circ-PRKCA [ 92 ] but upregulates miR-142-5p [ 93 ], miR-206 [ 94 ], and miR-192-5p [ 95 ]; in chronic myelogenous leukemia curcumin induces the miR-21-mediated modulation of the PTEN/AKT pathway, causing the inhibition of leukemic cell growth, both in vitro and in vivo [ 96 ], while in acute myeloid leukemia it inhibits the expression of the lncRNA HOTAIR and enhances the expression of miR-20a-5p [ 97 ]; in multiple myeloma it upregulates miR-101, thereby inhibiting EZH2 expression [ 98 ]; in colon cancer it downregulates both miR-130a [ 99 ] and miR-491 [ 100 ] but upregulates miR-137 [ 101 ], miR-200c [ 102 ], and miR-409-3p [ 103 ]; in melanoma it enhances the expression of miR-222-3p [ 104 ]; in pancreas cancer cells curcumin downregulates miR-199a and upregulates miR-22 [ 105 ]; in human prostate cancer stem cells, curcumin influences the expression of both miR-143 and miR-145 [ 106 , 107 ], and similarly to breast and gastric cancer it upregulates miR-34a [ 108 ]; in ovarian cancer, a curcumin derivative (ST09) deregulated the miR-199a-5p/DDR1 axis [ 109 ], while curcumin itself upregulates the lncRNA circ-PLEKHM3, promoting the intracellular depletion of miR-320a and suppressing cell proliferation and enhancing apoptosis [ 110 ]; in hepatocellular carcinoma it downregulates the expression of circ_0078710 (and consequently enhances miR-378b expression) [ 111 ] and downregulates miR-21-5p [ 112 ] and miR-21 [ 113 ]; in renal carcinoma, ...…”
Section: Effects Of Lifestyle On Ncrna Expression and Cancermentioning
confidence: 99%
“…Prior research has demonstrated that Cur possesses a range of anti-tumor [ 2 , 3 ], anti-cancer [ 4 , 5 ], anti-inflammatory [ 6 ], antioxidant [ 7 ], and anti-ischemic [ 8 ] pharmacological properties. In the context of tumor treatment, Cur has been shown to be capable of inducing apoptotic tumor cell death inhibiting the proliferative and invasive activity of these cells [ 9 , 10 , 11 , 12 ]. Importantly, Cur is broadly active against a range of tumor types and exhibits synergy with other anti-tumor compounds [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%